Water mites of the genus Limnesia Koch, 1836 (Acari: Hydrachnidia, Limnesiidae) from China, with description of four new species - Yi, Tianci; Jin, Daochao (Zootaxa, 2009)
Seven species of Limnesia Koch, 1836, from China are described or redescribed from newly collected material. Treated herein are four new species (Limnesia diploseta sp. nov., Limnesia turgeotrochanter sp. nov., Limnesia megaseta sp. nov. and Limnesia hirtigenitalia sp. nov.) as well as three previously known species (Limnesia maculata (Müller, 1776), Limnesia papillosa Viets, 1935 and Limnesia undulata (Müller, 1776)).